2014
DOI: 10.1590/s1413-70542014000500006
|View full text |Cite
|
Sign up to set email alerts
|

Water retention and s index of an oxisol subjected to weed control methods in a coffee crop

Abstract: Weed control in different crops affects the chemical, physical, and biological properties of the soil and consequently its structural quality. The objective of this study was to evaluate, using water retention characteristics and the S index, the physical quality of an Oxisol (Red-Yellow Latosol), subjected to weed control during the cultivation of coffee. The following weed control methods were evaluated: harrowing, brushcutting, residue crushing, manual weeding, post-emergence herbicide application, pre-emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…The biomass deposited maintains the superficial soil moisture and promotes fine root development (Pedrosa et al, 2014;Martinelli et al, 2017;Favarin et al, 2018;Franco Júnior et al, 2019;Resende et al, 2022). The inter-row cultivation of U. decumbens with coffee has favorable effects on soil physical and chemical characteristics, which leads to better development of the coffee root system (Siqueira et al, 2015) and increased water storage capacity under irrigation (Rocha et al, 2016). These changes also led to increased production.…”
Section: Coffee-urochloa Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…The biomass deposited maintains the superficial soil moisture and promotes fine root development (Pedrosa et al, 2014;Martinelli et al, 2017;Favarin et al, 2018;Franco Júnior et al, 2019;Resende et al, 2022). The inter-row cultivation of U. decumbens with coffee has favorable effects on soil physical and chemical characteristics, which leads to better development of the coffee root system (Siqueira et al, 2015) and increased water storage capacity under irrigation (Rocha et al, 2016). These changes also led to increased production.…”
Section: Coffee-urochloa Managementmentioning
confidence: 99%
“…Certain studies did not explicitly aim at evaluating the use of Urochloa as a coffee intercrop, but instead at weed control during the coffee planting. Although young coffee plants can suffer competition and have reduced growth (Araújo et al, 2012), significant benefits of intercropped Urochloa with coffee lines have also been described (Siqueira et al, 2015). The comparison of weed control methods, including mechanical, chemical (herbicide), and vegetation cover methods (like U. decumbens) showed that in addition to controlling weeds at the two depths analyzed (0-15 cm and 15-30 cm), there was an increase in soil pH, Ca and Mg contents, the sum of bases and cation exchange capacity, and organic matter content.…”
Section: Coffee-urochloa Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…• Agroforestry systems, cover crops, intercropping and mulching generally improve water infiltration and retention, and can improve drainage due to positive effects on soil physical properties and water retention (Siqueira et al, 2014). However, care should be taken to avoid too much competition with coffee plants for water, light or nutrients (Delgado et al, 2021;Neither et al 2017) showed that cocoa agroforestry systems and monocultures have distinct moisture dynamics, and that cocoa and shade trees in agroforestry systems use water resources complementarily.…”
Section: Improve Water Retention (Infiltration Storage)mentioning
confidence: 99%